2005
DOI: 10.1002/ptr.1588
|View full text |Cite
|
Sign up to set email alerts
|

Activity of aqueous extract of the bark ofVitex doniana on uterine muscle response to drugs

Abstract: The activity of Vitex doniana on the uterine muscle response was investigated. The bark of Vitex doniana was extracted in boiled water at 100 degrees C, and the extracted solution filtered and centrifuged with refrigeration. The extract prepared from the dry powder extract was tested on uterine muscle strip preparations. The bark extract of Vitex doniana was analysed elementally and found to contain much more potassium and phosphate than calcium, magnesium, zinc and iron. The presence of potassium ions in exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Nnajiofor, (2003) studied the fermentation of V. doniana (black plum) juice for the production of wine, while Agbede and Ibitoye, (2007) studied the sugar content as well as the anti-nutritional factor in its fruit. Egbekun et al, (1996) showed that V. doniana could serve as good source of nutritive sweetener while Ladeji et al, (2004) reported the anti diarrhoea effect of stem bark of V. doniana. Despite its use as food and medicine in this region, there has been little or no report on its proximate, vitamin and mineral composition.…”
Section: Introductionmentioning
confidence: 99%
“…Nnajiofor, (2003) studied the fermentation of V. doniana (black plum) juice for the production of wine, while Agbede and Ibitoye, (2007) studied the sugar content as well as the anti-nutritional factor in its fruit. Egbekun et al, (1996) showed that V. doniana could serve as good source of nutritive sweetener while Ladeji et al, (2004) reported the anti diarrhoea effect of stem bark of V. doniana. Despite its use as food and medicine in this region, there has been little or no report on its proximate, vitamin and mineral composition.…”
Section: Introductionmentioning
confidence: 99%
“…Phytocompounds have been earlier used for antiplasmodial activity (Samy et al, 2011). Some of the plants used in this study have been reported to have pharmacological properties (Atawodi 2005;Ladeji et al, 2005;Hassan et al, 2007;Okpanach, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…V. doniana is used in the treatment of conjunctivitis, skin rashes due to measles, chickenpox, respiratory infections and abdominal disorder and diarrhea. [5][6][7] Its antioxidant and anti-microbial activities against the methicillinresistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE) and multidrug-resistant Burkholderia cepacia and Pseudomonas aeruginosa are known. 8,9 Several other activities of the stem bark, leaves and fruits of black plum have been documented, however, the enormous phytochemical constituents in V. doniana are still underutilized.…”
Section: Introductionmentioning
confidence: 99%